Perawatan Horizontal Pluner Pump di Pertamina Hulu Energi Jambi Merang - Sudirnanto, Sudirnanto; Abryandoko, Eko Wahyu (Universitas Bojonegoro, 2022)
Pertamina Hulu Energi (PHE) Jambi Merang is a company that produces natural gas and condensate. The natural gas produced is sold to PLN in Jambi, South Sumatra and West Java as fuel for PLN and industry. Meanwhile, the condensate is exported to Singapore as industrial fuel. Because the pump is a vital equipment or component in a natural gas production process and to learn about reciprocating pumps and how to maintain them so that the pump can work optimally and be ready for use at any time. The purpose of this research is to understand about Preventive Maintenance (Preventive maintenance) on the Horizontal Plunger Pump and study the problems that often occur in the Horizontal Plunger Pump and how to solve them. The data collection methods used were direct researcher participation in the research object, field observations and interviews with the department responsible for managing the horizontal plunger pump at PERTAMINA HULU ENERGY JAMBI MERANG. From the results of the research conducted, it was found that the preventive maintenance work on the Horizontal Plunger Pump LP Flare KOD which was carried out at PHE Jambi Merang included weekly service, 3 month service, and 6 month service. In addition, problems that often occur with the Horizontal Plunger Pump at PHE Jambi Merang include the suction strainer often experiencing an increase in differential pressure, the rapid filling of the high level in the exhaust fluid storage tank from oil, seepage or leakage in the lubrication tank on the level indicator bar, noise on the V-Belt, excessive vibration or vibration, lube oil pressure to the stuffing box is often insufficient.